PENGARUH STRUKTUR KEPEMILIKAN, LIKUIDITAS DAN LEVERAGE TERHADAP FINANCIAL DISTRESS - Budiarso, Novi Swandari (ACCOUNTABILITY, 2014)
The purpose of this study was to determine the variables that contribute to financial distress at the manufacturing company. Another aim is to conclusion the solution for the financial distress, relation to the variable-variable: institutional ownership, liquidity and leverage.This  study  uses  secondary  data  obtained  from  Indonesia  Stock Exchange (BEI). During period 2010 to 2011. Data  used  in  this  study  include  financial  ratios  and ownership structure ratio. The  statistical  methods  used  to  test  the  hypothesis  is  logit model. The results of this study indicate that variable institutional ownership have a significant positif to financial distress, liquidity have a significant negative to financial distress, while leverage have no significant effect to financial distress